2001
DOI: 10.1007/s003840100358
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase gene polymorphism predicts response to capecitabine in advanced colorectal cancer

Abstract: Thymidylate synthase is a target enzyme for chemotherapeutic agents such as 5-fluorouracil and capecitabine, its oral prodrug. The human thymidylate synthase gene promoter is polymorphic, having either double or triple repeats of a 28-bp sequence. It has previously been shown that colorectal cancer patients who are homozygous for the triple tandem repeats (L/L) have significantly higher thymidylate synthase mRNA expression than those homozygous for the double repeat variant (S/S). Capecitabine is converted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 8 publications
4
53
2
3
Order By: Relevance
“…Although shown to be feasible in this setting, the three different measures of TS (genotype, IHC and expression) all appeared to be of limited use in predicting outcome to OSI-7904L. The data generated showed no correlation between the different measures themselves and unlike other groups, failed to predict outcome based on any of the markers examined (Johnston et al, 1995;Lenz et al, 1995;Park et al, 2002;Kawakami and Watanabe, 2003). This may be attributable to the fact that the majority of tumour samples were retrieved from the original diagnostic block (Johnston et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although shown to be feasible in this setting, the three different measures of TS (genotype, IHC and expression) all appeared to be of limited use in predicting outcome to OSI-7904L. The data generated showed no correlation between the different measures themselves and unlike other groups, failed to predict outcome based on any of the markers examined (Johnston et al, 1995;Lenz et al, 1995;Park et al, 2002;Kawakami and Watanabe, 2003). This may be attributable to the fact that the majority of tumour samples were retrieved from the original diagnostic block (Johnston et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Firstly, Park et al (2002) studied the relationship of the promoter polymorphism in the TS gene -a 28 base pair tandem repeat DNA present in two or three copies -with outcome in patients with colorectal cancer who received capecitabine therapy. While a small retrospective pilot study, they showed that patients with a 2/2 polymorphism may have superior outcome to those patients with 2/3 or 3/3 genotype.…”
mentioning
confidence: 99%
“…28 In another small retrospective study of 24 patients with metastatic colorectal cancer, three out of four homozygous TSER*2 patients responded on capecitabine, whereas only one out of 12 of heterozygotes and two out of eight homozygous TSER*3 patients responded. 29 Furthermore, in a study of 221 patients with Dukes C colorectal cancer, patients homozygous for TSER*3 gained no survival benefit from 5-FU treatment, whereas survival was increased in Pyrimidine antagonist pharmacogenetics JG Maring et al heterozygotes and patients homozygous for TSER*2. 30 However, the TSER genotype did not seem to be an efficacious marker for tumour sensitivity to 5-FU-based oral adjuvant chemotherapy in 135 Japanese colorectal patients.…”
Section: -Fluorouracilmentioning
confidence: 99%
“…An association between the genotype of the TS enhancer region and response and toxicity with 5-FU-based therapy in patients with colorectal cancer has been reported previously. [29][30][31][32][33][34][35][36][37][38][39] : patients who are homozygous for the double-tandem repeat have a lower TS protein content and a higher likelihood of response, but a greater risk of toxicity. MTHFR is involved in the regeneration of 5 methyltetrahydrofolate from 5,10 methylenetetrahydrofolate.…”
Section: Discussionmentioning
confidence: 99%